Ganze und meromorphe Lösungen einer Differenz-Differentialgleichung - Navickaitė, L. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Л. Навицкайте. Целые и мероморфные решения дифференциально-разностного уравнения L. Navickaitė. Diferencialinės-skirtuminės lygties meromorfiniai ir sveiki sprendiniai